Cytokine dysregulation despite immunoglobulin replacement therapy in common variable immunodeficiency (CVID) - Poto, Remo; Pecoraro, Antonio; Ferrara, Anne Lise; Punziano, Alessandra; Lagnese, Gianluca; Messuri, Carla; Loffredo, Stefania; Spadaro, Giuseppe; Varricchi, Gilda (Frontiers in Immunology, 2023)
Common variable immunodeficiency (CVID) is the most prevalent symptomatic primary immunodeficiency. CVID is a heterogeneous disorder with a presumed multifactorial etiology. Intravenous or subcutaneous immunoglobulin replacement therapy (IgRT) can prevent severe infections but not underlying immune dysregulation. In this study, we evaluated the serum concentrations of proinflammatory (TNF-α, IL-1β, IL-6) and immunoregulatory cytokines (IL-10), as well as lipopolysaccharide (LPS) and soluble CD14 (sCD14) in CVID individuals with infectious only (INF-CVID), and those with additional systemic autoimmune and inflammatory disorders (NIC-CVID), and healthy donors (HD). Our results showed increased serum concentrations of TNF-α, IL-1β, IL-6, and IL-10 in both INF-CVID and NIC-CVID subjects compared to HD. However, elevations of TNF-α, IL-1β, IL-6, and IL-10 were significantly more marked in NIC-CVID than INF-CVID. Additionally, LPS concentrations were increased only in NIC-CVID but not in INF-CVID compared to HD. Circulating levels of sCD14 were significantly increased in NIC-CVID compared to both INF-CVID and HD. These findings indicate persistent cytokine dysregulation despite IgRT in individuals with CVID. Moreover, the circulating cytokine profile reveals the heterogeneity of immune dysregulation in different subgroups of CVID subjects.